Factors Causing School Drop Outs in Nagari Tanjung Betung, Rao Selatan District, Pasaman Regency - Fera Adelia; Irmawita Irmawita (Universitas Negeri Padang, 2020)
This research is motivated by the large number of children who have dropped out of school in one of the Nagari in South Rao District, Nagari is Nagari Tanjung Betung. This is caused by several factors. The purpose of this research is to study and describe the factors that cause children to drop out of school in Nagari Tanjung Betung. This type of research uses a qualitative descriptive approach. The data sources in this study were 6 dropout children who were the main subjects, 6 parents of dropout children, Wali Nagari Tanjung Betung, and one of the Jorong Heads who were informants in this study. Data collection techniques used are observation, interviews, and documentation. Data recording techniques using voice recording devices. Data analysis was performed using a qualitative data analysis with data reduction, data presentation, and conclusion drawing processes. The data validity technique used is triangulation. Based on the data that has been collected the results of this study indicate that the factors that cause school dropouts in Nagari Tanjung Betung, Rao Selatan District Pasaman Regency are caused by 1) socioeconomic conditions in the family, based on the results of the study it was found that low family economy causes inability parents to pay for children in school 2) Interest in learning, loss of interest or interest in children in learning can be caused by factors that influence the influence of friends uncomfortable school conditions so that children are lazy to go to school 3) Motivation of children, loss of children's desire to go to school to a factor in school dropouts. 4) Problems at school, the many problems at school both from their own children and the school environment also affect dropouts. 5) Social environment, a bad social environment can have a bad influence on children which causes children no longer willing to go to school.Keywords: Factors Causing, School Dropouts